2001
DOI: 10.1097/00005176-200111000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Transmission of Hepatitis C Virus in a Cohort of 2,447 HIV-Seronegative Pregnant Women: A 24-Month Prospective Study

Abstract: This long-term prospective study shows that, although vertical transmission from HIV-negative mothers occurs in 13% of cases, there is a high rate of spontaneous viral clearance (75%). High maternal viral load and mothers belonging to HCV risk categories were the only variables predictive of the vertical transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
1
6

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 35 publications
(54 reference statements)
10
88
1
6
Order By: Relevance
“…44,[60][61][62][63] In one study, three fourths of the infants identified with mother-to-infant hepatitis C cleared the HCV RNA by 2 years of age. 23,64 In another study, all 5 infants with mother-to-infant hepatitis C lost detectable serum HCV RNA by 6 months of age. 65 Thus, outcome of mother-to-infant transmission of HCV is usually considered in terms of evolution to chronic hepatitis C, with later spontaneous clearance of HCV infection or progressive chronic liver disease.…”
Section: Outcome Of Mother-to-infant Hepatitis C In Affected Infantsmentioning
confidence: 98%
See 2 more Smart Citations
“…44,[60][61][62][63] In one study, three fourths of the infants identified with mother-to-infant hepatitis C cleared the HCV RNA by 2 years of age. 23,64 In another study, all 5 infants with mother-to-infant hepatitis C lost detectable serum HCV RNA by 6 months of age. 65 Thus, outcome of mother-to-infant transmission of HCV is usually considered in terms of evolution to chronic hepatitis C, with later spontaneous clearance of HCV infection or progressive chronic liver disease.…”
Section: Outcome Of Mother-to-infant Hepatitis C In Affected Infantsmentioning
confidence: 98%
“…No significant differences were found with spontaneous rupture of membranes, duration of membrane rupture, vaginal delivery or Cesarian section, or evident fetal distress. Infants tended to be small for gestational age, but this could not be attributed solely to maternal chronic hepatitis C. In a study of 2,447 HIVnegative pregnant women from Italy, 23 78 women were identified as anti-HCV positive and these mother-child pairs were monitored for 2 years; 60 women were found to be HCV RNA positive. Eight infants were identified as infected with HCV.…”
Section: Risk Of Spread Of Hcv Infection From Mother-to-childmentioning
confidence: 99%
See 1 more Smart Citation
“…15 This clearance is only surpassed by infants with vertically transmitted HCV who demonstrate the highest rate of spontaneous resolution at 75%. 16 A multicenter trial to address the efficacy of current HCV therapy with interferon and ribavirin in this patient population has been initiated. Reports of malaria 17 and West Nile virus [18][19][20][21] in the US blood supply suggests that blood safety cannot be completely ensured and that despite sensitive and specific testing, transfusion-related infections are still a concern.…”
Section: Transfusion-related Infectionsmentioning
confidence: 99%
“…Thus the influence of timing and mode of infection on the outcome of hepatitis C acquired in childhood remain to be clarified. Data from prospective studies on perinatally transmitted HCV infection are scanty [Tovo et al, 2000;Ceci et al, 2001], and the purpose of this multicenter study is to provide information on the outcome of infection and associated liver disease in a relatively large series of European children.…”
Section: Introductionmentioning
confidence: 99%